2017
DOI: 10.1177/8755123316686815
|View full text |Cite
|
Sign up to set email alerts
|

Developing Melodic Dictation Pedagogy: A Survey of College Theory Instructors

Abstract: The purpose of this study was to identify pedagogical approaches to melodic dictation used by college music theory instructors at National Association of Schools of Music accredited institutions. Instructors (N = 270) from 45 states responded to an online survey targeting melodic dictation instruction in their freshman theory courses. Results indicated that instructors: Chose pitch systems that emphasized scale degree function and rhythm systems that emphasized the meter, acknowledged the difficulty of compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Based on this relatively even split, the researchers recommended further investigation of the efficacy of these two strategies. In a related study, Paney and Buonviri (2017) found that 82% of college instructors of freshman music theory recommended listening before writing, and only 18% recommended writing while listening. College instructor survey participants appear to be more fully in agreement with each other, but the contrast to results of the AP Music Theory teachers is puzzling.…”
Section: Listening and Writingmentioning
confidence: 98%
See 1 more Smart Citation
“…Based on this relatively even split, the researchers recommended further investigation of the efficacy of these two strategies. In a related study, Paney and Buonviri (2017) found that 82% of college instructors of freshman music theory recommended listening before writing, and only 18% recommended writing while listening. College instructor survey participants appear to be more fully in agreement with each other, but the contrast to results of the AP Music Theory teachers is puzzling.…”
Section: Listening and Writingmentioning
confidence: 98%
“…His between-subjects design focused on music theory majors and consisted of three conditions (listening before writing, writing while listening, and listening, singing, and then writing). The findings of the two surveys by Buonviri and Paney (2015) and Paney and Buonviri (2017) suggest a need for research focused specifically on the efficacy of two dictation strategies: listening before writing and writing while listening. High school and early college students typically take dictation of tonal melodies, and a comparison of the two strategies for this particular task could provide more specific information to both high school and college instructors and students.…”
Section: Rationale For the Current Studymentioning
confidence: 99%
“…It is possible to mention approaches such as to think in isolated intervals among the notes; to observe scale degrees; to associate the notes to kinesthetic movements, similar to playing an instrument; or to execute gestural and/or vocal performances of rhythm or melody (Karpinski, 2000;Lake, 1993;Paney & Buonviri, 2014;Potter, 1990;Vargas & López, 2008). Considering strategies related specifically to melodic dictations, suggested by Ear Training instructors, some can be mentioned: to draft the rhythm before writing the pitches, or to draft the noteheads (i.e., pitches without rhythm), scale degrees, names of the notes, or the melodic contour before writing the rhythm; to focus attention during the listening only on the rhythm, or on the pitches, or on broader music aspects (e.g., contours, phrases); to first hear the dictation and only after write it down, or to write simultaneously with hearing; to write a little of the beginning and a little of the end of the melody, or to write the maximum possible of the beginning or of the end, or to use theoretical knowledge to make predictions about implied harmonies, pitches, and rhythms (Buonviri & Paney, 2015;Paney & Buonviri, 2017).…”
Section: Strategies For Dictation Takingmentioning
confidence: 99%
“…Music educators can benefit from practical classroom applications inspired by research to help students develop their aural skills. 15 For the purposes of this article, aural skills refers to taking dictation and sight-reading. This article includes practical applications drawn from the research for improving students' overall aural skills, with special consideration for minor tonality and compound meter.…”
Section: Where Do Students Struggle?mentioning
confidence: 99%